2022
DOI: 10.1108/lht-01-2022-0001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of VR-based product demonstrations featuring items of furniture

Abstract: PurposeThis paper aims to present a case study of virtual-reality-based product demonstrations featuring items of furniture. The results will be of use in further design and development of virtual-reality-based product demonstration systems and could also support effective student learning.Design/methodology/approachA new method was introduced to guide the experiment by confirming orthogonal arrays. User interactions were then planned, and a furniture demonstration system was implemented. The experiment compri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…New technologies, such as augmented reality (AR), mobile visual search and infographics, are now incorporated to strengthen library services (Lo et al , 2019; Suen et al , 2020; Li and Liu, 2022; Xin, 2022). Dalili Saleh et al (2022) studied the use of AR in medical libraries in universities and showed that AR could assist library management.…”
Section: Use Of Augmented Reality (Ar) and Visual Technologies For Di...mentioning
confidence: 99%
“…New technologies, such as augmented reality (AR), mobile visual search and infographics, are now incorporated to strengthen library services (Lo et al , 2019; Suen et al , 2020; Li and Liu, 2022; Xin, 2022). Dalili Saleh et al (2022) studied the use of AR in medical libraries in universities and showed that AR could assist library management.…”
Section: Use Of Augmented Reality (Ar) and Visual Technologies For Di...mentioning
confidence: 99%
“…In this issue, Xin (2024) shows that furniture products' interactive display through VR can improve learner satisfaction through quality design planning and help students better grasp the characteristics of products than paper catalogs, website catalogs and even online videos. Zhang (2024) shows that the relationship between players' motivation in AR-based games and the virtual community has a significant positive impact.…”
Section: Virtual Reality (Vr) Augmented Reality (Ar) and Education Gamesmentioning
confidence: 99%
“…In Wismer et al (2021), immersive VR simulations, as a promising training strategy, were used to teach practical professional skills in the biopharma industry. Furthermore, VR technologies have also revolutionized product demonstrations and prototyping, offering a more immersive and interactive experience that can improve efficiency and effectiveness (Xin, 2022; Halabi, 2020).…”
Section: Virtual Reality Technologymentioning
confidence: 99%